Higgs Domino Island Ditinjau Dari Hukum Pidana Islam - Fauzi, Mahmud; Harahap, Zul Anwar Ajim (Jurnal El-Thawalib, 2022)
This study discusses the Review of Islamic Criminal Law Against the Activities of Using the Higgs Domino Island Online Game which is a trend among today's society, the Higgs domino game is an online game that can generate cash by playing using chips as bets. Chip is a type of currency used in online games, and has a function as the value at stake in the Higgs Domino Island online game, so that with the element of betting, the author wants to examine how to use the Higgs Domino Island Online Game in SIhitang Village, Southeast Padangsidimpuan District, Padangsidimpuan City. , and how is the review of Islamic criminal law on the activity of using the Higgs Domino Island Online Game which aims to find out the law rather than the use of Higgs Domino Island according to Islamic criminal law. This game has a lot of impact on a person's lifestyle to make someone lazy to work and unproductive. Betting is included as one of the elements of gambling that can distract a person from remembering Allah swt and includes shaitanic acts, gambling is also an activity in which there are more harms than benefits. The gambling sanctions in Islamic criminal law are ta'zir sanctions whose determination is carried out by judges.